Panel data and structural labour market models - Bunzel, H. (Henning) (Amsterdam ; New York : Elsevier, 2000)
Panel Data and Structural Labour Market Models is the latest volume in a series of four, reporting on the original work of an international group of scholars with research interests in the performance of the labour markets that condition the dynamic labour market experiences of individual workers. The book contains papers focusing on theoretical and empirical modelling of the labour market covering both wage equilibrium models and models for labour market transition. Contributions range from the theoretical or econometric through empirical structural methods and exploratory data analysis based on employer and employee level data. Academic libraries, labour economists, labour and industrial relations research institutes and statistical agencies will find this a particularly useful piece of work.
Three elements of personnel policy : worker flows, retention and pay / Niels Westergaard-Nielsen -- Equilibrium search with human capital accumulation / Lars Korsholm -- Employer pay policies and male retirement decisions / G. Lanot -- Search friction in the U.S. labor market : equilibrium estimates from the PSID / Shannon N. Seitz -- Estimating the intertemporal elasticity of substitution in a model with household production : implications for macroeconomics / Randall Wright -- Monte Carlo EM-algorithms for the proportional hazards model with grouped duration data / Laxs Muus -- Econometric analysis of dynamic panel data models : a growth theory example / S. Aiyar -- A structural model of labor market histories with duration dependence and endogenous search / M.-Y. An -- Insiders versus outsiders and endogenous search / Birthe Larsen -- The simple analytics of partnership formation / Melvyn G. Coles -- Equilibrium unemployment with wage posting : Burdett-Mortensen meet Pissarides / Dale T. Mortensen -- The relation between wages and labor market frictions : an empirical analysis based on matched worker-firm data / Kaxsten Albaek -- Job destruction and wage dynamics / George R. Neumann -- The equilibrium search model with productivity dispersion and structural unemployment : an application to Danish data / Michael Rosholm -- An introduction to panel data and structural labour market models / Dale T. Mortensen.
Papers presented at a conference.
Includes bibliographical references.
Description based on print version record.
Keywords: Labor market -- Congresses; Labor supply -- Congresses; Unemployment -- Congresses; Business & Economics -- Labor; Business & Economics -- Management; Labour economics